(untitled) (Proceedings of Faculty of Civil Engineering, 2025)
The article examines the application of Computational Fluid Dynamics (CFD) in the analysis of physical, chemical and biological processes in wastewater treatment. The use of CFD in wastewater treatment enables detailed simulation and visualization of fluid flow, mixing, and chemical reactions within treatment units, which helps optimize design and operational parameters. CFD can identify inefficiencies, such as dead zones or short-circuiting in tanks, and support improvements in aeration, sedimentation and chemical dosing. By reducing the need for physical prototyping and trial-and-error adjustments, CFD contributes to cost savings, enhanced treatment performance, and more sustainable system development. The aim of the paper is to highlight the application of CFD in the design, optimisation and analysis of wastewater treatment plants and to encourage wider application in professional and educational settings.